How can patient registries facilitate guideline-based healthcare? A retrospective analysis of the CEDATA-GPGE registry for pediatric inflammatory bowel disease - M. Leiz; M. Knorr; K. Moon; L. Tischler; K. Sohrabi; S. Cantez; J. Däbritz; J. de Laffolie; N. van den Berg; CEDATA GPGE Study Group (BMC, 2023)
Abstract Background Early diagnosis is mandatory for the medical care of children and adolescents with pediatric-onset inflammatory bowel disease (PIBD). International guidelines ('Porto criteria') of the European Society for Pediatric Gastroenterology, Hepatology and Nutrition recommend medical diagnostic procedures in PIBD. Since 2004, German and Austrian pediatric gastroenterologists document diagnostic and treatment data in the patient registry CEDATA-GPGE on a voluntary basis. The aim of this retrospective study was to analyze whether the registry CEDATA-GPGE reflects the Porto criteria and to what extent diagnostic measures of PIBD according to the Porto criteria are documented. Methods Data of CEDATA-GPGE were analyzed for the period January 2014 to December 2018. Variables representing the Porto criteria for initial diagnostic were identified and categorized. The average of the number of measures documented in each category was calculated for the diagnoses CD, UC, and IBD-U. Differences between the diagnoses were tested by Chi-square test. Data on possible differences between data documented in the registry and diagnostic procedures that were actually performed were obtained via a sample survey. Results There were 547 patients included in the analysis. The median age of patients with incident CD (n = 289) was 13.6 years (IQR: 11.2-15.2), of patients with UC (n = 212) 13.1 years (IQR: 10.4-14.8) and of patients with IBD-U (n = 46) 12.2 years (IQR: 8.6-14.7). The variables identified in the registry fully reflect the recommendations by the Porto criteria. Only the disease activity indices PUCAI and PCDAI were not directly provided by participants but calculated from obtained data. The category 'Case history' were documented for the largest part (78.0%), the category 'Imaging of the small bowel' were documented least frequently (39.1%). In patients with CD, the categories 'Imaging of the small bowel' (χ2 = 20.7, Cramer-V = 0.2, p < 0.001) and 'Puberty stage' (χ2 = 9.8, Cramer-V = 0.1, p < 0.05) were documented more often than in patients with UC and IBD-U. Conclusion The registry fully reproduces the guideline's recommendations for the initial diagnosis of PIBD. The proportion of documented diagnostic examinations varied within the diagnostic categories and between the diagnoses. Despite technological innovations, time and personnel capacities at participating centers and study center are necessary to ensure reliable data entry and to enable researchers to derive important insights into guideline-based care.